Personality and pro-environmental behaviour in the workplace: a Big Five perspective - Lau, Jasmine Leby; Jamaluddin, A. (Knowledge Words Publications, 2024)
This study investigates the association between Big Five personality traits and Organisational Citizenship Behaviour toward the Environment (OCBE) within the workplace context. A two-step hierarchical regression approach was employed to elucidate the predictive power of both demographic variables and Big Five traits on OCBE. In the initial step, demographic variables were introduced into Model 1 and the outcome showed that education and recycling habits significantly predicted OCBE. However, in Model 2, which focused solely on the Big Five traits, conscientiousness emerged as the sole significant predictor of OCBE. These findings highlight the pivotal role of education, personal recycling habits and conscientiousness trait in fostering organisational citizenship behaviours. This could be achieved through interventions and training programmes designed to promote and facilitate environmentally friendly behaviours both within home and workplace settings. Such initiatives have the potential to cultivate a more proactive and engaged workforce, thereby fostering a positive organisational culture that values sustainability.